Leucose enzoótica bovina: isolamento de amostras brasileiras do vírus e obtenção de antígeno - Grazielle Cossenzo Florentino (2014)
Bovine leukemia virus presents a worldwide distribution and commonly affects dairy cattle causing economical losses related to increased heifer replacement costs, loss of income from condemned carcasses of cull cows, reduced fertility and decreased milk production. Diagnostic techniques recommended by the World Organization for Animal Health (OIE) are agar gel immunodiffusion test (AGID) and the enzyme linked immunosorbant assay (ELISA). In Brazil there is a commercially available IDGA test (IDGA-Cm) is based on antigen produced by a fetal lamb kidney (FLK) cell line persistent infected with BLV and bovine viral diarrhea virus. ELISA tests to BLV are not commercially available in Brazil, and the cost associated to import process prevents its use in large scale in the country. The aims of this study were to: 1. isolate BLV from peripheral blood mononuclear cells from naturally infected cows using the cell line Tb1lu, which is BVDV-free; 2. produce an antigen from Brazilian BLV isolates; 3. compare the IDGA developed in this study with the IDGA-Cm and the commercially available ELISA. Seven PBMC samples positive for BLV by reverse-transcriptase PCR were used for viral isolation attempt using Tb1lu cell. Four of seven samples were isolated as conformed by PCR and electron microscopy. One isolate was select for antigen production and development. One hundred and eighty samples from two field BLV positive. The antigens A and B were less sensitive compared to ELISA. BLV were successfully isolated from field samples using the Tb1lu cells, and used for the development of a in-house IDGA.